Analisis Peran Budaya Lokal dalam Materi Ajar pada Pembelajaran Bahasa Indonesia di Tingkat SD/MI - Muzfirah, Suci (Wulang: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Language teaching materials, especially Bahasa Indonesia for elementary school age learners (SD/MI) is very meaningful especially aimed at learning to speak words both in writing and oral, thus making students who are able to apply good speech in the community. Indonesian language learning at SD/MI level is expected to be able to improve students' skills in order to be able to interact and generate appreciation for the work of literature and culture of the Indonesian state. Local culture in the surrounding environment is very important in the process of teaching and learning Bahasa Indonesia. Students often face difficulties in pursuing Bahasa Indonesia material because the teacher taught is quite boring. This research uses descriptive quadrative research method with library study approach. The object of study in this study is the role of local culture in teaching materials in Indonesian language learning. An educator, especially a teacher, must realize that Indonesian language learning is learning about language skills and not learning about language regulation. By incorporating local cultural values, it is expected that the teaching materials in Bahasa Indonesia will become very interesting to learn. The integration of local cultures in teaching materials in Indonesian language learning will play an important role for students in acting in speech that holds the noble values of Indonesian culture and the learning process will be very interesting for students in SD/MI.